Effect of ethanol on performance and durability of a diesel common rail high pressure fuel pump - Mickevičius, Tomas; Slavinskas, Stasys; Kreivaitis, Raimondas (Transport, 2016)
This paper presents a comparative experimental study for determining the effect of ethanol on functionality of a high pressure pump of the common rail fuel injection system. For experimental durability tests were prepared two identical fuel injection systems, which were mounted on a test bed for a fuel injection pump. One of the fuel injection systems was feed with diesel fuel; other fuel injection system was fuelled with ethanol–diesel fuel blend. A blend with 12% v/v ethanol and 88% v/v diesel fuel and low sulphur diesel fuel as a reference fuel were used in this study. To determine the effect of ethanol on the durability of the high pressure pump total fuel delivery performance and surface roughness of pump element were measured prior and after the test. Results show that the use of the ethanol–diesel blend tested produced a negative effect on the durability of the high pressure fuel pump. The wear of plungers and barrels when using ethanol–diesel fuel blend caused a decrease in fuel delivery up to 30% after 100 h of operation.First published online: 13 Jul 2015